GERAKAN DIGITAL ADVERTISING SEBAGAI UPAYA MEMBANGKITKAN PEREKONOMIAN SITUASI COVID-19 MELALUI PELATIHAN DIGITAL MARKETING - Erlin Elisa; Tukino Tukino; Alfannisa Annurullah Fajrin; Rika Harman (ASOSIASI IDEBAHASA KEPRI, 2023)
Indonesia confirmed its first case of infection with the corona virus that causes Covid-19 in early March 2020. Since then, various countermeasures have been carried out by the government to reduce the impact of the Covid-19 pandemic in various sectors. Indonesia's economic activity was hampered due to Covid-19 which ultimately had an impact on state revenues. Likewise, the city of Batam, which is one of the cities in the Riau Archipelago district, the city of Batam, which incidentally is located on the border with neighboring Singapore and Malaysia, is of course an advantage, one of which is in the economic sector, but since Covid-19 hit and access has become limited in various fields. and the situation is that the income of Batam residents has greatly decreased which has had a huge impact on the people's economy coupled with the increase in layoff rates which has exacerbated the situation. This community service activity aims to provide digital marketing training to young men and women who are starting a home industry in one of the residential areas in the city of Batam. Due to the impact of the pandemic, the activities of residents engaged in home industry businesses have also been affected, therefore we, as educators, through community service activities, go out into the field with the aim of providing knowledge in the form of digital marketing training with the aim that this home industry can awaken and develop return to business that had died down.